Potential Presymptomatic Transmission of SARS-CoV-2, Zhejiang Province, China, 2020 - Tong, Zhen-Dong; Tang, An; Li, Ke-Feng; Li, Peng; Wang, Hong-Ling; Yi, Jing-Ping; Zhang, Yong-Li; Yan, Jian-Bo (Emerging infectious diseases, 2020)
We report a 2-family cluster of persons infected with severe acute respiratory syndrome coronavirus 2 in the city of Zhoushan, Zhejiang Province, China, during January 2020. The infections resulted from contact with an infected but potentially presymptomatic traveler from the city of Wuhan in Hubei Province.